Integration of Molecular Factors Influencing VCAM-1 Expression in Vascular Inflammation and Atherosclerosis: A Narrative Review - Nur Asini; Taufik Indrajaya; Irfannuddin; Siti Sarahdeaz Fazzaura Putri (International Journal of Science and Society, 2026)
Vascular Cell Adhesion Molecule-1 (VCAM-1) is a vascular adhesion molecule that plays a crucial role in vascular inflammation, endothelial dysfunction, and the development of atherosclerosis. Increased VCAM-1 expression occurs in response to various inflammatory stimuli and cellular stressors that involve the activation of specific molecular signaling pathways. Various factors such as chronic inflammation, oxidative stress, activation of the Nuclear Factor-kappa B (NF-κB) pathway, the Janus Kinase-Signal Transducer and Activator of Transcription (JAK-STAT) pathway, obesity, leptin resistance, genetic factors, and changes in vascular hemodynamics are known to contribute to increased VCAM-1 expression. This study aims to analyze various factors that influence VCAM-1 changes molecularly using a narrative review method. Article searches were conducted through the PubMed, Scopus, and Google Scholar databases using the keywords "VCAM-1", "NF-κB", "oxidative stress", "LEPR", "leptin resistance", "endothelial dysfunction", and "atherosclerosis". The articles used were published between 2020 and 2026, relevant to the research topic, and available in full text. The review results indicate that NF-κB activation is the primary mechanism of VCAM-1 elevation triggered by pro-inflammatory cytokines, increased reactive oxygen species (ROS), leptin resistance, and LEPR activation via the JAK-STAT pathway. Furthermore, genetic factors such as LEPR polymorphisms and epigenetic mechanisms also contribute to increased vascular inflammation and VCAM-1 expression. Thus, VCAM-1 has great potential as a biomarker of vascular inflammation and a therapeutic target in cardiovascular disease, particularly atherosclerosis.